Macroalgae Community Structure on Different Substrate in Sabang Waters - Darlina; Saida Rasnovi; Amalia (Postgraduate, University of Mataram, 2025)
Research on analysis of macroalgae community structure on different substrates in Sabang waters to identify, analyzing diversity, abundance, and important value index. The data collection method was carried out by purposive sampling using a plot of 1x1 m2 with 10 plots per transect. Sampling was carried out at three stations, namely Station I on Pasir Putih with a medium fine sand substrate, Station II at Anoi Itam with a gravel sand substrate, and Station III on Rubiah Island with a fine sandy clay substrate. Data were analyzed using the Importance Value Index (IVI) and the Shannon-Wiener Diversity Index. The environmental parameters at each station that were measured were substrate particles, temperature, brightness, depth, and current velocity, while the chemical parameters were salinity, pH, COD, phosphate, and nitrate. The results of the study found 2615 macroalgae individuals consisting of three divisions. Chlorophyta division consists of 9 species, Rhodophyta was 7 species, and Phaeophyta was 1 species (Dyctyota dichotoma). The highest Important Value Index at each research station consisted of the Chlorophyta division with two species, namely Dictyosphaeria cavernosa (IVI = 59.18) and Halimeda opuntia (IVI = 54.15). The value of the diversity index (H') of macroalgae in Sabang waters is moderate, namely in Pasir Putih as much as 2.18, Anoi Itam and Rubiah Island as much as 2.01, and 1.97, respectively. The study concluded that the macroalgae community structure in Sabang waters exhibits moderate species diversity, with the Chlorophyta division, particularly Dictyosphaeria cavernosa and Halimeda opuntia, showing the highest importance value indices across different substrates.